Padrão de tamanho do corpo das espécies de cladóceros continentais do Novo Mundo : importância das relações filogenéticas, do espaço e do ambiente. - Leal, Clarice Maria (2015)
Several studies have shown that species of cladocerans in tropical regions are smaller than those who inhabit temperate regions, and environmental is one of the most studied factors to explain this pattern. However, the historical aspects may also to influence on the pattern of morphological characters of the species, since usually the species are not independent as to the character. This study evaluated the existence of phylogenetic signal in the mean body size of cladocerans species continental of the New World, the influence of phylogenetic relationships, space and environment on this pattern, and the association of the individual responses of each species, independent of phylogeny, and environment. Whereas many features of cladocerans remained unchanged during the evolutionary history of the group, it is believed that the phylogenetic signal in body size is an important factor to explain this pattern front of the importance of space and environment. We considered occurrence data of 242 species obtained from studies conducted in the American continent. Analyses were performed considering the distances between species in relation to phylogeny, space and environment. The presence of phylogenetic signal was detected in body size of the species when considered those closest in the phylogeny. Phylogenetic relationships were the most important factor to explain the body size of species of cladocerans. The association between the ecological component of body size for pelagic species and environment, independent of phylogeny, suggests a recent adaptive response of the species of this group to current temperature conditions.